2002
DOI: 10.1002/ijc.10612
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the quantitative measurement of the oncoprotein p185Her‐2/neu in a group of patients with breast cancer and positive node involvement

Abstract: Our study attempts to determine the prognostic value of the quantitative measurement of the oncoprotein p185Her-2/neu in a group of patients with breast cancer and positive node involvement. In a series of 217 patients with breast cancer and positive nodes in whom the oncoprotein p185 was quantitatively determined by ELISA, we analyzed the clinicopathological variables including age, menopausal status, tumor size, number of affected nodes, type and histology grade and the molecular variables such as the oestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Since previous reports have shown that HER2 overexpression and/or amplification does not exhibit a clear correlation to cathepsin D levels in breast cancers [31][32][33], it seems unlikely that results obtained for the analyzed group of patients reflect differences between triplenegative (ER -/PR -HER2-) and HER2-positive tumors. Taken together, these data suggest that, within the ER -/PR -phenotype, there might be a singular, biologically-related difference between patients with different nodal statuses or tumor sizes.…”
Section: Discussionmentioning
confidence: 43%
“…Since previous reports have shown that HER2 overexpression and/or amplification does not exhibit a clear correlation to cathepsin D levels in breast cancers [31][32][33], it seems unlikely that results obtained for the analyzed group of patients reflect differences between triplenegative (ER -/PR -HER2-) and HER2-positive tumors. Taken together, these data suggest that, within the ER -/PR -phenotype, there might be a singular, biologically-related difference between patients with different nodal statuses or tumor sizes.…”
Section: Discussionmentioning
confidence: 43%
“…In previous ELISA studies on tissue extract from breast carcinomas, this value was chosen in compliance with several criteria, such as validation according to the percentages of positives within the range of the cases observed by using gene amplification or overexpression of HER-2/neu in breast carcinomas (Valeron et al 1997;Koscielny et al 1998;Bohn et al 2002) or in cell lines (Konecny et al 2003;Konecny et al 2004), defined as the highest level of expression in non-malignant tissue (Piffanelli et al 1996), or as an intermodal value of a bimodal distribution of the oncoprotein levels (Eppenberger-Castori et al 2001). In the present work, we have investigated the clinical interest of all the obtained values of HER-2/ neu cytosolic levels.…”
Section: Discussionsupporting
confidence: 43%
“…Nevertheless, we consider that the large sample size in the present study allowed us to overcome some of the potential limitations introduced by stromal cell or DCIS contaminations in the ELISA. Our results are in accordance with prior studies where HER-2/neu was also determined in cytosolic samples of breast carcinomas using ELISA, and reporting an association between the elevated concentration of the oncoprotein and different parameters indicative of tumor aggressiveness, such as ductal histology and poorly differentiated histological grades (Bohn et al 2002), as well as with shortened relapse-free and/or overall survival (Nugent et al 1992;Eissa et al 1997;Bohn et al 2002;Konecny et al 2003Konecny et al , 2004. In addition, our results indicate that HER-2/neu cytosolic levels are significantly associated with aneuploidy and with higher Sphase fraction in breast carcinomas.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Overexpression of HER2/neu has also been shown to correlate with tumor grade, tumour size, lymph node metastasis, survival and resistance to hormonal therapy and chemotherapy in breast cancer patients (Korkolis et al, 2004;Fehm et al, 2004;Guarneri et al, 2004). An intact kinase domain is essential for activation of numerous downstream effectors, including phospholipase Cγ, PI3K/AKT and ERK1/2, which result in DNA synthesis and cell proliferation (Bohn et al, 2002;Alimandi et al, 1997;Montgomery et al, 2005;Price et al, 1999). The known oncogenic potential of HER2/neu and its high level of expression in tumour tissues when compared with that in normal tissues make this oncoprotein an ideal target for antitumour therapies (Fig.…”
Section: Introductionmentioning
confidence: 47%